Incorporation of antibiotics and systemic steroids by sinus surgeons: is there widespread consensus?. Issue 9 (6th July 2018) - Arianpour, Khashayar; Svider, Peter F.; Guys, Nicholas; Shenouda, Kerolos; Folbe, Elana; Hsueh, Wayne D.; Eloy, Jean Anderson; Folbe, Adam J.
Abstract : Background: The objective of this work was to evaluate factors associated with antibiotic and oral corticosteroid (OCS) prescription among otolaryngologists regularly performing sinus surgery. Methods: Fellowship‐trained rhinologists, including fellowship directors, were identified via the American Rhinologic Society (ARS) website. Non–fellowship‐trained otolaryngologists performing ≥25 balloons (frontal/maxillary) or ≥25 functional endoscopic sinus surgeries (FESSs) (frontal/maxillary/ethmoids) were also included in "balloon surgeons" and "sinus surgeon" cohorts, respectively. Prescribing data for Medicare Part D beneficiaries was obtained for 2015. Results: Otolaryngologists included in this analysis wrote a median of 54 scripts for antibiotics, with a 15.1% antibiotic prescription rate. The overall script length per antibiotic was 11.1 days. Of fellowship‐trained rhinologists, 90.2% wrote fewer than 100 scripts, compared to 25.6% and 32.5% of sinus surgeons and balloon surgeons, respectively. Fellowship‐trained rhinologists wrote lengthier antibiotic scripts (14.1 vs 10.3 days, p < 0.05). Clinicians who have been in practice longer prescribed antibiotics significantly more frequently. Fellowship‐trained rhinologists had a greater OCS rate (8.9%) than balloon and sinus surgeons (7.1%), also writing lengthier courses (15.0 vs 8.1 days). Early‐career otolaryngologists wrote lengthier steroid prescriptions than those with 11 to 20 years and >20 years in practice. Conclusion: Antibiotic and OCS utilization varies by type of training, as non–fellowship‐trained sinus surgeons and balloon surgeons tend to utilize antibiotics more aggressively, and fellowship‐trained rhinologists utilize OCS more frequently. Otolaryngologists with more years in practice are more likely to incorporate antibiotics in the management of sinus disorders, although these conclusions must be considered in the context of this resource's limitations. Further clarification of guidelines may be helpful for minimizing divergent practices and maintaining a consensus.